Comprehensive nursing intervention for postoperative scar management in preschool children with congenital melanocytic nevus - Fan, Xing; Qiao, Yanxia; Sun, Lida; Zhang, Yurong; Wu, Shuping (Frontiers in Pediatrics, 2025)
BackgroundSurgical excision of congenital melanocytic nevi (CMN) in preschool children is essential for minimizing oncogenic risk and improving cosmetic outcomes. However, such procedures often lead to hypertrophic scarring, which can negatively impact physical appearance and psychological well-being during critical developmental stages. Traditional postoperative care tends to overlook the psychosocial dimension, underscoring the need for holistic interventions.ObjectiveThis study aimed to assess the efficacy of a comprehensive nursing intervention comprising scar massage therapy, silicone gel sheet application, and structured psychological counseling on enhancing postoperative recovery in preschool children undergoing CMN excision. Outcomes evaluated included scar quality, wound healing time, psychological well-being, complication rates, and parental satisfaction.MethodsIn this prospective observational cohort study, preschool children undergoing CMN excision received either a comprehensive nursing care pathway or usual postoperative care, as implemented in routine practice. Outcomes (VSS, PedsQL, healing time, complications, and parental satisfaction) were assessed at baseline and 1, 2, 4, and 8 weeks. Between-cohort differences were analyzed with appropriate tests and multivariable adjustment for baseline covariates.ResultsThe comprehensive care group were significantly higher VSS scores (3.2 ± 0.7 vs. 5.5 ± 0.8, p < 0.05), shorter healing time (3.5 ± 0.6 vs. 5.2 ± 0.7 weeks), higher PedsQL scores (80.5 ± 4.2 vs. 72.3 ± 3.8), lower complication rates (5.0% vs. 8.0%), and higher parental satisfaction (90% vs. 70%).ConclusionsA multidimensional nursing intervention appears to improve both physical and psychological postoperative outcomes in pediatric CMN patients. Integrating scar management with emotional support represents a best-practice approach for optimizing recovery and quality of life.